1983
DOI: 10.1111/j.1476-5381.1983.tb10544.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histamine and the histamine antagonists mepyramine and cimetidine on human coronary arteries in vitro

Abstract: 1The effects of histamine have been studied on human isolated coronary artery preparations taken from hearts ranging in age from 9 to 73 years. 2 Histamine in large concentrations (100 jiM) contracted arteries which were without tone or spontaneous activity and sometimes induced rhythmic contractile activity. If spontaneous rhythmic activity was present it was enhanced by histamine. The contractile effects of histamine were inhibited by mepyramine but not by cimetidine. 3 Arteries which were contracted by depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…In ring preparations of isolated rabbit mesenteric arteries, we have observed that histamine elicits mepyramine-sensitive contractions ; indicating an action via HI receptor activation as previously reported for other blood vessels (Godfraind and Miller, 1983; Van de Voorde and Leusen, 1984;Toda, 1986). The present study shows a competitive antagonism of histamine-mediated responses by cicletanine, comparable to observations in guinea-pig ileum (Schoeffter et al, 1987) and human coronary artery (Schoeffter and Godfraind, 1988); thus suggesting an action via H1 receptors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In ring preparations of isolated rabbit mesenteric arteries, we have observed that histamine elicits mepyramine-sensitive contractions ; indicating an action via HI receptor activation as previously reported for other blood vessels (Godfraind and Miller, 1983; Van de Voorde and Leusen, 1984;Toda, 1986). The present study shows a competitive antagonism of histamine-mediated responses by cicletanine, comparable to observations in guinea-pig ileum (Schoeffter et al, 1987) and human coronary artery (Schoeffter and Godfraind, 1988); thus suggesting an action via H1 receptors.…”
Section: Discussionsupporting
confidence: 86%
“…It could be reasoned that the biphasic response to histamine in cicletamine-treated rings is a sum of 2 possible actions on the (-) and (+)-enantiomem of cicletanine in the racemic mixture employed. The distribution of histamine receptors on endothelial and smooth muscle cells has been reported to show both tissue as well as speciesspecificity (Godfraind and Miller, 1983; Van de Voorde et al, 1984;Abacioglu et al, 1987). 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal portions (about 2 cm) of the anterior descending branch of the left coronary artery and circumflex coronary artery were removed and cleaned of all loosely adherent tissue. Rings of artery (about 2 mm wide) were suspended in 50 ml organ baths in physiological solution (composition millimolar: NaC1,112;KCI,5;NaHCO,,25;KH~POI,0.1;MgS04,0.12;CaC12,1.25;and glucose,11.5) maintained at 37" and aerated with a gas mixture of 95% 0 2 and 5% C02 under a resting tension of 2 g. The presence of endothelium in these preparations was demonstrated by their relaxant response to histamine (Godfraind & Miller 1983b;Van de Voorde & Leusen 1983). Sixteen rings were prepared from each heart.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using selective histamine-receptor agonists and antagonists have demonstrated the presence of coronary vasoconstricting H, receptors and vasodilating H 2 receptors in isolated epicardial vessels. '-2 -2 *" 31 When coronary blood flow is the measured variable, in situ and in vivo data indicate that histamine-induced increases are mediated by both H, and H 2 receptor. 4 -3 -32 - 33 While this apparent disparity in findings has produced some confusion, it does suggest a basis for the separate regulation and responsiveness of epicardial conductance and distal resistance arteries.…”
Section: Discussionmentioning
confidence: 99%